Health and social factors associated with a delayed discharge amongst inpatients in acute geriatric wards: A retrospective observational study - Romero-Ortuno, Roman (My University, 2018)
Aim: In the English National Health Service there is an increasing interest in understanding the factors associated with delayed discharges in older hospitalized adults. The present study sought to analyze whether clinical frailty was a significant and independent risk factor for having a delayed discharge when the data were controlled for potential health and social confounders. Methods: This was a retrospective observational study in an English National Health Service teaching hospital. We analyzed all first hospitalization episodes to the Department of Medicine for the Elderly between 1 May 2016 and 31 July 2016. A delayed discharge was operationally defined as a patient being discharged more than 24 h after his/her last recorded clinically fit date. Results: A total of 924 cases were analyzed. The independent risk factors for having a delayed discharge were: needing a new package of care (OR 4.05, 95% CI 2.68–6.10), new institutionalization (OR 2.78, 95% CI:1.67–4.62), living alone (OR 1.98, 95% CI 1.40–2.81), delirium (OR 1.79, 95% CI 1.17–2.74) and frailty (i.e. ≥5 on the Clinical Frailty Scale, OR 1.74, 95% CI 1.15–2.63). Conclusions: The present results are consistent with previous reports that delayed discharges in older hospitalized patients are mainly related to new formal social care requirements in survivors of acute illness. Frailty was an independent risk factor for delay, but its effect might have been confounded by the unmeasured variable of informal care requirements. Our operational definition of delayed discharge does not mirror the legal definition of delayed transfer of care in England, and the results are not externally valid
Frailty and Delayed Discharge
PUBLISHED
Keywords: English National Health Service; older hospitalized adults; delayed discharges; Frail older adults; Hospital medicine; Informal care; Patient discharge; Social service; Ageing